Assessment of parasymphysis and ramus fractures in pediatric patients using panoramic radiographs and CBCT: a case report - Mahindra Awwaludin Romdlon; Fahri Reza Ramadhan; Lusi Epsilawati; Diera Fitrah Kusumawardhany (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: This case report aims to identify fractures that occur through panoramic radiographs and evaluated by CBCT after being given treatment. Case Report: A 12-year-old male patient came with his older brother to the emergency room (ER) RSKGM/Bandung Dental Hospital due to the trauma of a fall by an iron football goalpost while playing soccer which caused the patient to fall onto the grass field. The patient was experiencing continuous bleeding. Systemic and allergic history was denied. Extraoral examination showed bruising with no facial asymmetry. Intraoral examination revealed a vertical gap between teeth 42 and 43, the jaw within the site was mobile, and active bleeding especially from lingual lacerations. After consulting with Dental Surgery Specialist, the emergency room doctor gave interdental wiring. After 2 months post wiring, a CBCT photo evaluation was carried out. Conclusion: The mandibular fracture in this case report was well identified by clinical examination and supported by panoramic radiography. After that the patient was given treatment and evaluated through CBCT. CBCT provides a clearer and better picture.